Total factor productivity and convergence: evidence from old and new EU member countries’ banking sectors - Kasman, Adnan; Kasman, Saadet; Ayhan, Duygu; Torun, Erdost (Journal of Business Economics and Management, 2013)
This paper examines whether there has been convergence of total factor productivity levels across twenty-two EU member and three candidate countries following the process of legislative harmonization. The results indicate evidence of β-convergence and σ-convergence in productivity across sampled countries. The results further indicate that all sampled banking sectors seem to have experienced a significant productivity growth over the sample period. The productivity growth levels range from 3.1% to 15.6% and 6.8% to 19.5% in the old member and new member states, respectively. The geometric means considering all banking firms in the new member and candidate countries together reveal that banking sectors in these countries were more productive than those of in the old EU member countries. Overall, the evidence indicates that promoting merger and acquisition activities in the banking system (and hence supporting market driven consolidation of smaller banks) and enhancing the presence of foreign banks could increase competition and productivity in these banking systems.